2014
DOI: 10.1016/j.jtcvs.2014.06.045
|View full text |Cite
|
Sign up to set email alerts
|

Topical vancomycin in combination with perioperative antibiotics and tight glycemic control helps to eliminate sternal wound infections

Abstract: Topical vancomycin applied to the sternal edges, in conjunction with perioperative antibiotics and tight glycemic control, helps to eliminate wound infections in cardiac surgical patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
65
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 25 publications
3
65
2
Order By: Relevance
“…Local application of vancomycin, in addition to intravenous (IV) prophylactic antibiotics and tight glycaemic control, has been shown to be very effective to substantially decrease the incidence of sternal wound infection after cardiac surgery [125] and may become recommended part of multifaceted prophylactic strategy to prevent sternal wound infections. There are however concerns regarding potentially high serum levels and the risk of selection of resistant strains to this important antibiotic.…”
Section: Prophylactic Antibiotic Therapy Perioperative Antimicrobialmentioning
confidence: 99%
“…Local application of vancomycin, in addition to intravenous (IV) prophylactic antibiotics and tight glycaemic control, has been shown to be very effective to substantially decrease the incidence of sternal wound infection after cardiac surgery [125] and may become recommended part of multifaceted prophylactic strategy to prevent sternal wound infections. There are however concerns regarding potentially high serum levels and the risk of selection of resistant strains to this important antibiotic.…”
Section: Prophylactic Antibiotic Therapy Perioperative Antimicrobialmentioning
confidence: 99%
“…Some reports emphasize that more efforts should be taken to prevent it rather than to treat it, especially for those patients who have high risk factors such as obesity, comorbidities of diabetes mellitus, or chronic obstructive pulmonary disease. [4,5] However, the introduction of various flaps has led to a significant decrease in morbidity and mortality over the past 30 years. [6] According to the severity and dimensions of the DSWI, the therapeutic methods range from conservative treatment to radical surgical debridement followed by negative pressure wound therapy or 1-stage flap coverage.…”
Section: Introductionmentioning
confidence: 99%
“…The rate of superficial SSI (defined as an infection occurring within 30 days of the procedure, which involves only skin and subcutaneous tissue of the incision, and has pain, edema, erythema, or tenderness; purulent drainage; organisms isolated from aseptically-obtained culture; or diagnosis by the surgeon) has been reported to occur in 1% to 4% of cardiac surgery patients undergoing median sternotomy. [1][2][3] Mediastinitis is a feared complication of these procedures and previously was reported to occur in approximately 1% of patients, although a more recent series put this figure at 0.23%. 2,4,5 Several studies have shown significantly reduced long-term survival associated with this wound complication.…”
mentioning
confidence: 99%